A STUDY OF MUSICAL STRUCTURE AND PANTUN TEXTS IN JONGGAN PERFORMING ARTS AMONG DAYAK KANAYATN - Olendo, Yudhistira Oscar; Syam, Christanto; Utama, Indra (Universitas Tanjungpura, 2023)
Jonggan is a popular performance art in the Kanayatn Dayak community in West Kalimantan. Jonggan is a traditional art form that has been passed down from generation to generation within the Kanayatn Dayak community. The performance combines music, dance, and poetic recitation to provide entertainment. With the rapid development of technology, the role of musicians in a performance has diminished. The contemporary Jonggan performance has changed in terms of (1) dance movements, (2) costumes, (3) the presence of whistle blowers, and (4) the use of a curtain. In the 1960s and 1970s, Jonggan was still present, but since the 1980s, it has almost disappeared, especially among millennial, and when it is performed, it has undergone transformations. Nowadays, there is a term called Jongset (Jonggan Kaset), which refers to Jonggan performed using cassette tapes (cassette tapes = CD, DVD, or music files on a flash drive), which has eliminated the essence of traditional musical instruments. This raises the question of how the musical structure of the pantun accompaniment, including melody and rhythm, is incorporated into the Jonggan performance art. The research method employed in this study is a descriptive qualitative approach with a musicological perspective. Data can be directly observed from the current existence of Jonggan. The results of the research on the musical structure of the pantun accompaniment in the Jonggan performance aim to preserve and document traditional music materials in a more organized manner. Jonggan can become a cultural-based performance industry with economic impacts (creative economy). The musical structure of Jonggan uses instruments such as agukng, dau, gadobokng, and soling.